2016
DOI: 10.1051/matecconf/20166501003
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Gearbox Fault Diagnosis by Vibration Measurements

Abstract: Abstract.Vibration analysis has been demonstrated to be one of the best tools to detect faults in a gearbox by providing abundant information about the operating condition of a gearbox. However, a gearbox generates complex vibration signals, which makes it difficult to diagnose when a fault occurs. There are several fault diagnosis methods that can be utilized to analyze the underlying signals. The time-frequency method has been used and showed some promising results. On the other hand, it also has its drawbac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…A study reviewing these methods concluded that vibration‐based methods provide the best practices for wind turbines SHM. Consequently, the use of structural vibration of gearboxes, blades, and tower positioning provide a simple basis for measuring the unbalanced parameters for potential and pre‐existing fatigue damage. A critical comparative analysis of these contact and noncontact sensors is explored in Table with respect to their determination of in‐field unbalanced vibrational parameters (radial displacement and modal frequency) …”
Section: State Of the Art In Classical Contact And Noncontact Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study reviewing these methods concluded that vibration‐based methods provide the best practices for wind turbines SHM. Consequently, the use of structural vibration of gearboxes, blades, and tower positioning provide a simple basis for measuring the unbalanced parameters for potential and pre‐existing fatigue damage. A critical comparative analysis of these contact and noncontact sensors is explored in Table with respect to their determination of in‐field unbalanced vibrational parameters (radial displacement and modal frequency) …”
Section: State Of the Art In Classical Contact And Noncontact Sensorsmentioning
confidence: 99%
“…In other studies, other novel indirect contact approaches to determine unbalanced parameters using prognostic methods are indicated. They include gearbox monitoring using vibration analysis and time‐series prediction, bearings acoustic emission, use of signature distances, and supervisory control and data acquisition (SCADA) data analysis.…”
Section: State Of the Art In Classical Contact And Noncontact Sensorsmentioning
confidence: 99%
“…Thus, the application of this algorithm allows you to change the frequency and acceleration values smoothly within a wide range and, thus, does not exceed the permissible limits on acceleration [12,13]. …”
Section: ) Hardware Partmentioning
confidence: 99%
“…The development of the metal-working equipment designs led to the further development of information and measurement technology [11][12][13][14] for vibration diagnostics of the technological system "machine-tool-tool-instrument-piece".…”
Section: Introductionmentioning
confidence: 99%
“…There are known the designs of the mobile diagnostic complexes of foreign and domestic origin as well as their application techniques [11][12][13][14]. These complexes show good results, but they are complicated to operate (instruction and special skills are required) that determined the necessity to develop an up-to-date, compact, reliable and easy-to-use diagnostic system for vibration diagnostics.…”
Section: Introductionmentioning
confidence: 99%